Corporate Planning for Kuala Lumpur City Securities Sdn. Bhd. - Yong, Wooi Kee (1999)
Kuala Lumpur City Securities Sdn Bhd ( KLCS ) had been using different strategies to achieve the desired profits since it commenced business in 1992. For the past 6 years many different plans had been used. InitialJy the company used trial and error method in order to achieve the desired profit, later Yearly Business Plans were being used by the company. Under the Yearly Business Plan, a few different plans might be implemented during a year in order to achieve the planned profit. This was because plans were concentrated on certain areas based on seasonal situations. When the situations changed, the plans became ineffective and failed to achieve the desired profit. Then another plan was formulated within a short time and then implemented in order to achieve the desired profit within the remaining period. A lot of effort had been put in planning. However the planing was not comprehensive and was short-term. In the 1 997 financial crisis, there were several uncertainties in the whole business environment and the company was totally lost for direction. There were two-transactions done during that period and the transactions became overdue doubtful accounts now. The doubtful account was too huge and it may wipe out all the profits made earlier or even sink the whole company. The shareholders came to know about the doubtful accounts and demanded the Board of Directors to submit a comprehensive long-term plan in order to for them to have a clear direction of the business within one month for the shareholders extra ordinary general meeting's approval.